Coxiella burnetii associated with BVDV (Bovine Viral Diarrhea Virus), BoHV (bovine herpesvirus), Leptospira spp., Neospora caninum, Toxoplasma gondii and trypanosoma vivax in reproductive disorders in cattle - Zanatto, Diego Carlos Souza [UNESP]; Gatto, Igor Renan Honorato [UNESP]; Labruna, Marcelo Bahia; Jusi, Marcia Mariza Gomes; Samara, Samir Issa [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (FapUNIFESP (SciELO), 2019)
This is a cross-sectional study to assess the presence of antibodies in ruminants against selected pathogens associated with reproductive disorders in cattle in four Brazilian states, including the zoonotic agent Coxiella burnetii. The used tests were Virus Neutralization Assay for IBR and BVD, Microscopic Agglutination Test for Leptospira spp., Indirect Fluorescent Antibody Test (IFAT) for C. burnetii and Toxoplasma gondii, and Enzyme-Linked Immunosorbent Assay for Neospora caninum and Trypanosoma vivax. Seropositivity for C. burnetii was 13.7% with titers from 128 to 131,072; 57.8% for BoHV-1, with titers between 2 and 1,024; 47.1% for BVDV-1a, with titers from 10 to 5,120; 89.2% for N. caninum; 50% for T. vivax; and 52.0% for Leptospira spp., with titers between 100 to 800 (the following serovars were found: Tarassovi, Grippotyphosa, Canicola, Copenhageni, Wolffi, Hardjo, Pomona and Icterohaemorrhagiae); 19.6% for T. gondii with titer of 40. This is the first study that has identified C. burnetii in cattle associated with BoHV and BVDV, N. caninum, Leptospira spp., T. gondii and T. vivax. Thus, future studies should be conducted to investigate how widespread this pathogen is in Brazilian cattle herds.
Coxiella burnetii associada ao BVDV (Vírus da Diarreia Viral Bovina), bohv (vírus do herpes bovino), Leptospira spp., Neospora caninum, Toxoplasma gondii e trypanosoma vivax em distúrbios reprodutivos em bovinos
Keywords: Abortion; Cattle; Coxiella burnetii; Q Fever